PRODUCTION OF LIGHT HYDROCARBONS USING ZINC (Zn)-BASED ZEOLITE CATALYSTS (International journal of artificial intelligence, 2026)
The growing global demand for clean and efficient energy sources has intensified research into catalytic processes for converting feedstocks into valuable hydrocarbons. Among these, the production of light hydrocarbons using zinc (Zn)-based zeolite catalysts has gained significant attention due to its high efficiency, selectivity, and environmental advantages. This study explores the synthesis, characterization, and application of Zn-modified zeolite catalysts in the conversion of various feedstocks, including methanol, ethanol, and light alkanes, into light hydrocarbons such as ethylene, propylene, and butenes. The role of zinc in enhancing catalytic activity, improving aromatization, and influencing product selectivity is analyzed. The research also reviews existing literature, discusses reaction mechanisms, and evaluates industrial applicability. The findings demonstrate that Zn-based zeolite catalysts significantly improve hydrocarbon yield and selectivity, making them promising candidates for sustainable chemical production.